STRATEGI POLRES DALAM PENGUNGKAPAN TINDAK PIDANA KORUPSI DI BANDARA TUNGGUL WULUNG CILACAP - Sukarni Anggraeni (MIH Unsoed, 2018)
ABSTRACTCorruption is the cause of the onset of the economic crisis, undermine the legal system and inhibit the operations of a Government that is clean and democratic. In other words, corruption is already in the pivotal joints and country life. Therefore, corruption can no longer be classified as ordinary crimes but is already a tremendous crime.Methods of Juridical Normative approach is used, with discriptif analytical research specifications. The data source is secondary, and data were analyzed qualitatively.Strategic leadership of the national police in it, that the eradication of criminal acts of Corruption is a priority for the Police. The role of the Police here to be very important, because Police spearheading in law enforcement, though in its development in addition to Police and prosecutors, the State formed the other agencies specifically addressing criminal acts of Corruption eradication Commission i.e. Corruption (KPK). This is because the criminal offence of corruption is a crime which is an extra ordinary crime and have very large implications for lates the progress of countries, also most of the perpetrators of corruption are on the red tape that holds the power so in need of institutions superbodi in order to get past the existing regulation.Keywords: Police, corruption, law enforcement